Identification and characterization of repetitive extragenic palindromes (REP)-associated tyrosine transposases: implications for REP evolution and dynamics in bacterial genomes - Nunvar, Jaroslav; Huckova, Tereza; Licha, Irena (BMC genomics, 2010)
BACKGROUND: Bacterial repetitive extragenic palindromes (REPs) compose a distinct group of genomic repeats. They usually occur in high abundance (>100 copies/genome) and are often arranged in composite repetitive structures - bacterial interspersed mosaic elements (BIMEs). In BIMEs, regularly spaced REPs are present in alternating orientations. BIMEs and REPs have been shown to serve as binding sites for several proteins and suggested to play role in chromosome organization and transcription termination. Their origins are, at present, unknown. RESULTS: In this report, we describe a novel class of putative transposases related to IS200/IS605 transposase family and we demonstrate that they are obligately associated with bacterial REPs. Open reading frames coding for these REP-associated tyrosine transposases (RAYTs) are always flanked by two REPs in inverted orientation and thus constitute a unit reminiscent of typical transposable elements. Besides conserved residues involved in catalysis of DNA cleavage, RAYTs carry characteristic structural motifs that are absent in typical IS200/IS605 transposases. DNA sequences flanking rayt genes are in one third of examined cases arranged in modular BIMEs. RAYTs and their flanking REPs apparently coevolve with each other. The rayt genes themselves are subject to rapid evolution, substantially exceeding the substitution rate of neighboring genes. Strong correlation was found between the presence of a particular rayt in a genome and the abundance of its cognate REPs. CONCLUSIONS: In light of our findings, we propose that RAYTs are responsible for establishment of REPs and BIMEs in bacterial genomes, as well as for their exceptional dynamics and species-specifity. Conversely, we suggest that BIMEs are in fact a special type of nonautonomous transposable elements, mobilizable by RAYTs.
Keywords: konzervovaná sekvence; fylogeneze; Conserved Sequence; Phylogeny; obrácené repetice; Genome, Bacterial; Bacteria; molekulární sekvence - údaje; Amino Acid Sequence; molekulární evoluce; Evolution, Molecular; sekvenční seřazení; Transposases; tyrosin; transposasy; genom bakteriální; otevřené čtecí rámce; Inverted Repeat Sequences; Tyrosine; sekvence aminokyselin; Open Reading Frames; Molecular Sequence Data; Sequence Alignment